Kapok-Derived Super Hollow Porous Carbon Fibers and Their Greenhouse Gases Adsorption - Hun-Seung Jeong; Cheol-Ki Cho; Dong-Chul Chung; Kay-Hyeok An; Byung-Joo Kim (Fibers, 2025)
Industrialization and modernization have significantly improved the quality of life but have also led to substantial pollution. Cost-effective technologies are urgently needed to mitigate emissions from major polluting sectors, such as the automotive and transport industries. In this study, we synthesized naturally derived, kapok-based porous carbon fibers (KP-PCFs) with hollow structures. We investigated their adsorption/desorption behavior for the greenhouse gas n-butane following ASTM D5228 standards. Scanning electron microscopy and X-ray diffraction analyses were conducted to examine changes in fiber diameter and crystalline structure under different activation times. The micropore properties of KP-PCFs were characterized using Brunauer–Emmett–Teller, t-plot, and non-localized density functional theory models based on N2/77K adsorption isotherm data. The specific surface area and total pore volume ranged from 500 to 1100 m2/g and 0.24 to 0.60 cm3/g, respectively, while the micropore and mesopore volumes were 0.20–0.45 cm3/g and 0.04–0.15 cm3/g, respectively. With increasing activation time, the n-butane adsorption capacity improved from 62.2% to 73.5%, whereas retentivity (residual adsorbate) decreased from 6.0% to 1.3%. The adsorption/desorption rate was highly correlated with pore diameter: adsorption capacity was highest for diameters of 1.5–2.5 nm, while retentivity was greatest for diameters of 3.5–5.0 nm.